2018
DOI: 10.1071/rdv30n1ab101
|View full text |Cite
|
Sign up to set email alerts
|

101 Effects of Active Immunization Against GnRH in Oocyte Donors with Cystic Ovarian Disease

Abstract: Cows intensively used as oocyte donors for in vitro embryo production (IVEP) are usually kept nonpregnant for prolonged intervals, exposed to successive hormonal treatments, and frequently become overweight. These are all risk factors for the development of endocrine unbalance and, consequently, cystic ovarian disease (COD). The aim of this study was to evaluate the effect of active immunization against gonadotropin-releasing hormone (GnRH) on (1) ovarian follicular population, and (2) development potential of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In Experiment 2, most donors had varied records of chronic COD and refractoriness to conventional GnRH or P4 treatments, so they were treated with an anti-GnRH vaccine. Previous studies have shown that cows receiving either GnRH immunization or GnRH agonist, despite having suppressed follicle growth, can be used as oocyte donors and produce embryos in vitro 14,48 . Therefore, we decided to include a group with FSH priming, and thus we could not use the same experimental model as in Experiment 1.…”
Section: Endpointmentioning
confidence: 99%
See 2 more Smart Citations
“…In Experiment 2, most donors had varied records of chronic COD and refractoriness to conventional GnRH or P4 treatments, so they were treated with an anti-GnRH vaccine. Previous studies have shown that cows receiving either GnRH immunization or GnRH agonist, despite having suppressed follicle growth, can be used as oocyte donors and produce embryos in vitro 14,48 . Therefore, we decided to include a group with FSH priming, and thus we could not use the same experimental model as in Experiment 1.…”
Section: Endpointmentioning
confidence: 99%
“…The cows underwent a gynecological exam by B-mode and color Doppler ultrasonography to characterize ovarian status. To control for the potential detrimental effects of COD, cows were treated with two injections of an anti-GnRH vaccine (Bopriva, Zoetis Saúde Animal, São Paulo, Brazil), given 30 days apart, as previously described 14 . Twenty days later, cows were re-evaluated and were distributed in a balanced manner according to ovarian antral follicle count (AFC) into one of the following experimental groups: a) control group (CG), intraovarian injection of saline; b) intraovarian injection of MSC (treatment in both ovaries); or c) injection of MSC after priming with 150 IU FSH (Pluset, Hertape Calier Saúde Animal, Juatuba, Brazil).…”
Section: Animals and Locationmentioning
confidence: 99%
See 1 more Smart Citation